Geochemistry and rock magnetic analysis on surface sediment in Lampenisu River: a quest for Mg source to Lake Towuti, Indonesia (Rudarsko-geološko-naftni zbornik, 2022)
Sediment from Lake Towuti has been extensively studied to reconstruct past climate and environmental changes. One of the remaining questions is the source of magnesium (Mg) and calcium (Ca) in the northern part of Lake Towuti. In this study, the source of high Mg and Ca content is examined by analysing surface sediment from the Lampenisu River (LR) and Mahalona River (MR) that merge before entering Lake Towuti. Twelve surface sediments from MR, LR, and the confluence of the two rivers (LMR) were subjected to geochemical (XRF), mineralogical (XRD), and rock magnetic (susceptibility and hysteresis parameter) analyses. The result shows that the Mg and Ca content in LR samples are higher than in MR samples. LR samples have a higher susceptibility and a lower frequency dependent susceptibility than MR samples. XRD analyses on extracted magnetic grains show the presence of minerals with a sodalite crystal structure, possibly valleyite in LR but not in MR samples. If valleyite indeed occurs in LR samples, it may contribute to their relatively high Ca content. At the same time, the high content of Mg in LR samples is likely due to the serpentinized peridotite rocks. LR is thereby considered to be the source of high Mg and Ca content in the northern portion of Lake Towuti. This study shows the importance of sediment-source identification in big lakes such as Lake Towuti, where the influx could come from several rivers around the lake.